IKIGAI AMONG THE PEOPLE OF LANGKAWI ISLAND - Sazali, Noor Syahirah; Paidi, Rohayati (WILAYAH: The International Journal of East Asian Studies, 2023)
This research has proposed to determine how Langkawi Island people perceived worthwhile life in (ikigai) the face of pandemic challenges. To assess their level of ikigai (energy or strength to continue living or moving forward), current research employs three constructs: satisfaction, significance, and happiness. A combination of modified Q-method, the Time-use Survey based on the Questionnaire A of the 2021 Survey on Time-use and Leisure Activities, the English version of Ikigai-9, and the elements of the Ikigai Venn Diagram were used to build the research instruments. The five-page Q-data sheet was distributed to 24 participants which were selected using stratified sampling. The outcome implies that not all the locals’ ikigai were affected during the pandemic. Some of them even experienced an increase in ikigai during the period. Overall, the study also confirms that being able to do what we want to do is linked with an increase in life satisfaction, significance and happiness and eventually linked to an increase in well-being.